Business Cycle in Agriculture in Poland - Andrzej Jedruchniewicz (German Journal of Agricultural Economics (GJAE), 2020)
The main objective of the study was to characterize the business cycle and its particular phases in Polish agriculture and compare with the features of the cycle occurring in theory. The research for the years 2001-2015 which was based on annual real changes in final output allowed to identify three full cycles in Polish agriculture: 1) 2001-2006; 2) 2007-2010; 3) 2011-2015. The analysis of fluctuations showed that all cycles lasted from 4 to 6 years. Growth phases took from 2 to 4 years, and all downward ones lasted 2 years. The amplitudes of these phases were similar. There were both turning points and turning zones in the cycles. The analysis of accumulated dynamics of production, income, prices and investments in particular phases of the business cycle in Polish agriculture shows that in each growth phase all categories have increased. In almost all cycles, the dynamics of these categories in the growth phase was greater than the changes during the downturn. According to the theory of the classical cycle, the value of production as well as agricultural prices changed the most. They had negative dynamics in almost every downward phase. On the other hand, the dynamics of agricultural incomes was positive in all downward phases. Therefore, changes in this category in most cases had the features of the modern cycle. Changes in investments in the downward phases were diversified. The analysis of dynamics indicates that agricultural income and investments in Poland was also affected by the Common Agricultural Policy.
Keywords: 330